2013
DOI: 10.1007/s40333-013-0203-x
|View full text |Cite
|
Sign up to set email alerts
|

Human induced dryland degradation in Ordos Plateau, China, revealed by multilevel statistical modeling of normalized difference vegetation index and rainfall time-series

Abstract: Land degradation causes serious environmental problems in many regions of the world, and although it can be effectively assessed and monitored using a time series of rainfall and a normalized difference vegetation index (NDVI) from remotely-sensed imagery, dividing human-induced land degradation from vegetation dynamics due to climate change is not a trivial task. This paper presented a multilevel statistical modeling of the NDVI-rainfall relationship to detect human-induced land degradation at local and lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Drescher 1995;Yang et al 2006;Sternberg 2008;Le Polain de Waroux and Lambin 2012;Zhang et al 2014); however, dryland rehabilitation experiences or research at landscape level are much less common (e.g. Dorrough and Moxham 2005;Ravi et al 2009) and often refer to protected landscapes (e.g.…”
Section: Rehabilitation Of Degraded Dryland Ecosystemsmentioning
confidence: 99%
“…Drescher 1995;Yang et al 2006;Sternberg 2008;Le Polain de Waroux and Lambin 2012;Zhang et al 2014); however, dryland rehabilitation experiences or research at landscape level are much less common (e.g. Dorrough and Moxham 2005;Ravi et al 2009) and often refer to protected landscapes (e.g.…”
Section: Rehabilitation Of Degraded Dryland Ecosystemsmentioning
confidence: 99%
“…To prevent and reverse this degradation, a series of ecological protection and restoration projects have been implemented in many countries (Cao, 2011;Doren et al, 2009;Petursdottir et al, 2013), notably in China. Evidences have shown that these projects have helped to restore vegetation cover (Zhang et al, 2014a), and increase the net primary production and grassland yield (Fan et al, 2010). However, their positive effects appear to vary over space and time (Qi et al, 2013;Zhou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The identified variation is primarily related to human interferences, such as urbanization, land use policies and ecological projects (Li et al, 2012). As a novel method, the RESTREND has been proved to be a reliable indicator of human-induced vegetation variation (Wessels et al, 2007), and mainly been applied to identify land degradation in precipitation controlled regions (Wessels et al, 2007;Zhang et al, 2014a). However, its application in the temperature and precipitation jointly controlled environments was not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Land use activities have a considerable influence on the people, posing serious consequences for social, economic and ecological aspects of human society (Burchinal, 1989;FAO, 1997). The alteration in ecological and economic functions due to the decrease in the productivity and quality of the land (Hill et al, 2005) can lead to decline in the biological productivity of land due to climate change and human activities (Zhang et al, 2014). Land degradation poses a great threat to food security and damages the environmental safety of land as well as influences the sustainable development of society and economy .…”
Section: Introductionmentioning
confidence: 99%